2020
DOI: 10.1002/cae.22252
|View full text |Cite
|
Sign up to set email alerts
|

Weighted word embeddings and clustering‐based identification of question topics in MOOC discussion forum posts

Abstract: Massive open online courses (MOOCs) are recent and widely studied distance learning approaches aimed at providing learning material to learners from geographically dispersed locations without age, gender, or race-related constraints. MOOCs generally enriched by discussion forums to provide interactions among students, professors, and teaching assistants. MOOC discussion forum posts provide feedback regarding the students' learning processes, social interactions, and concerns. The purpose of our research is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
0
21
0
1
Order By: Relevance
“…Text classification by simple RF is the goal of [ 84 ]. Onan and Toçouglu [ 85 ] present a method for document clustering and topic modeling on massive open online courses. Sentiment analysis of technical words in English by the Gini index for feature selection is done by [ 86 ].…”
Section: Related Workmentioning
confidence: 99%
“…Text classification by simple RF is the goal of [ 84 ]. Onan and Toçouglu [ 85 ] present a method for document clustering and topic modeling on massive open online courses. Sentiment analysis of technical words in English by the Gini index for feature selection is done by [ 86 ].…”
Section: Related Workmentioning
confidence: 99%
“…Bao et al [20] proposed a SC-Net using semantic coherence for machine-generated spam text detection. In addition, some methods based on data mining and analysis [21][22][23], weighted word embedding [24][25][26], keyword extraction [27], and machine learning [28,29] have been proposed.…”
Section: Related Workmentioning
confidence: 99%
“…e results revealed that teacher, content, assessment, and schedule had significant effects on student satisfaction. Onan et al developed a document-clustering model based on weighted word embedding to identify question topics on posts of MOOC forum [12]. Later, Onan designed a long short-term memory networks (LSTM) to classify the sentiment for about 70,000 MOOC reviews, which can achieve a high classification accuracy [13].…”
Section: Literature Reviewmentioning
confidence: 99%